Pengaruh Pemberian Jus Kurma Terhadap Kemajuan Kala II Persalinan Primigravida di Tempat Praktek Mandiri Bidan Cintia Kota Bandung - Dian Siti Awali; Cintia Dewi Abdurachman; Evi Kusumahati (Jurnal Kesehatan Rajawali, 2023)
Normal labor is the process of expelling fetus that occurs in full-term pregnancy, and complications of labor one of causes, kala II lengthens, especially primigravida mothers, oral intake with dates during labor, dates are nutritious fruits that rich in carbohydrates, simple sugars that easily absorbed by body. This study aims to determine the effect of giving date juice on the duration of labor in the second stage of primigravida labor. Using Experimental research model, namely Quasi-Experiment with pretest-postest research design with control group design. Sampling was done by purposive sampling technique. The sample was primigravida mothers many 15 Intervention and 15 Control mothers. The difference in average duration of labor in intervention group mean (12.87) with SD (4.688) minutes, while in the control group mean (36.20) with SD (9.244) minutes means that intervention group is 5 minutes shorter than the control group. Results of Data Analysis Data normality test using the Shapiro-Wilk test that data is normally distributed. The results of independent t-test analysis of 0.00 < α (0.05) show that there is an effect of giving date palm juice on duration of labor phase II in primigravida laboring mothers at the Cintia Midwife Independent Practice Place in Bandung City.